Naldemedine versus placebo in opioid-induced constipation: a meta-analysis - Wobbe, Bastian; Gerner, Maximilian; Koehne, Claus-Henning (BMJ Supportive & Palliative Care, 2022)
ObjectiveOpioid-induced constipation (OIC) is a frequent adverse event among patients receiving chronic pain therapy that is requiring opioids. Naldemedine was approved by the Food and Drug Administration to treat OIC and appears to be more efficient than any other peripherally acting mu-opioid receptor antagonist. This meta-analysis aimed at assessing the available data on naldemedine in terms of efficacy. MethodsWe searched the Cochrane Library, PubMed and ClinicalTrials on 24 May 2022 to identify randomised controlled trials (RCTs) comparing naldemedine to placebo among patients reporting OIC. ResultsEvaluation of 6 RCTs enrolling 2769 participants showed significantly greater respondence to treatment (OR=2.48; 95% CI: 2.02 to 3.06; p<0.00001), change in weekly spontaneous bowel movements (SBMs) (mean difference=1.45; 95% CI: 1.14 to 1.76; p<0.00001), complete SBMs (mean difference=0.89; 95% CI: 0.62 to 1.17; p<0.00001) and SBMs without straining (mean difference=0.89; 95% CI: 0.61 to 1.17; p<0.00001) for patients treated with naldemedine. We found no difference in numeric pain rating scales after one (mean difference=0.05; 95% CI: -0.22 to 0.31; p=0.73) and two weeks of treatment (mean difference= -0.04; 95% CI: -0.31 to 0.22; p=0.75). Funding and clinical diversity were possible risks of bias. ConclusionsNaldemedine improves a variety of bowel function parameters while preserving analgesia, confirming its efficacy for patients with OIC. However, head-to-head trials are needed to establish naldemedine as treatment of first choice for laxative-refractory OIC. PROSPERO registration numberCRD42022281353.
CRIS-Team WoS Importer:2023-01-13